STRATEGI MEMBANGUN KESADARAN PENERAPAN SYARI’AH ISLAM MELALUI DAKWAH EKSTRAPARLEMENTER - Edi Sabara Manik; Hasanuddin Hasanuddin (AL-FIKRA, 2017)
Islam is the perfect religion that governs the relationship between man and his god (ibadah), man with his fellow man (muamalah) and relationship with himself. This rule is what is meant by Shari'ah. However, today the Muslims can only practice the rules that are ibadah, while muamalah that is implemented today is not in accordance with the Shari'ah. Therefore, there should be a da’wah in openness to Muslims so that they are aware of the problem of the application of shari'ah in all kinds of life. One of the most powerful and open movement of da'wah in the struggle for Islamic Shariah is Hizbut Tahrir Indonesia (HTI). This movement is a non-Minstream movement that was established on Al-Quds Palestine and Indonesia in the 1980s through a cleric from Hizb ut-Tahrir, DR. Abdurrahman Al-Baghdadi. The strategy of hizbut tahrir in carrying out its da'wah activities by opening up, accepting everyone to become a cadre, hizbut tahrir approach from technocrats, students, academics, intellectuals and even they also do pandekatan entrepreneurs who can accept their da'wah idea. Its da'wah strategy through culture and structural or political, this is the strategy of da'wah from other Islamic mass organizations. However, his political strategy is an extraparalementer.